Silver nanorod: green synthesis and their electronic, optical and antibacterial properties - Pant, Rojita; Shrestha, Sabita (Scientific World, 2024)
Synthesis of nanomaterials has been the subject of a lot of interests due to its commercial demands and wide applicability in various fields such as chemistry, physics, biology, material science, engineering, medicine etc. This paper reports the green synthesis of silver nanorod. For synthesis, silver nitrate solution was used as a metal precursor and aqueous extract of root of Beta vulgaris was used as a reducing agent. Four different sets of samples were synthesized by varying the reduction time to study the size dependent electronic and optical properties. The formation of nanostructure was confirmed by presence of surface plasmon resonance in absorption spectra. Optical band gap calculation was done by using absorption spectroscopy. Absorption spectroscopy showed that the maximum absorption was red shifted when the reaction time was increased, indicating the increasing size of material. Similarly, it was found that the optical band gap was decreased with increasing reduction time. Moreover, the antimicrobial activity of synthesized nano silver was studied against both the gram negative (Pseudomonas aeruginosa, Escherichia coli) as well as gram positive bacteria (Staphylococcus aureus).